2008
DOI: 10.1534/genetics.108.090407
|View full text |Cite
|
Sign up to set email alerts
|

A Genomewide Linkage Scan for Quantitative Trait Loci Influencing the Craniofacial Complex in Baboons (Papio hamadryas spp.)

Abstract: Numerous studies have detected significant contributions of genes to variation in development, size, and shape of craniofacial traits in a number of vertebrate taxa. This study examines 43 quantitative traits derived from lateral cephalographs of 830 baboons (Papio hamadryas) from the pedigreed population housed at the Southwest National Primate Research Center. Quantitative genetic analyses were conducted using the SOLAR analytic platform, a maximum-likelihood variance components method that incorporates all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Quantitative genetics has helped illuminate our understanding of the genetic architecture that underlies continuously variable phenotypes of the vertebrate skeleton, including the cranium (e.g., Cheverud and Buikstra, 1981;Cheverud, 1982;Leamy et al, 1999;Hlusko, 2004;Sherwood et al, 2008aSherwood et al, , 2008bRoseman et al, 2010). The vertebrate cranium is comprised of three major developmental components: the splanchnocranium (comprising the jaws, hyoid, and middle ear bones) the chondrocranium (supporting the brain and sensory organs) and the dermatocranium (comprising the roof and sides of the cranium) (Kardong, 1995;Hildebrand and Goslow, 2001;Webster and Webster, 2013).…”
Section: Craniofacial Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative genetics has helped illuminate our understanding of the genetic architecture that underlies continuously variable phenotypes of the vertebrate skeleton, including the cranium (e.g., Cheverud and Buikstra, 1981;Cheverud, 1982;Leamy et al, 1999;Hlusko, 2004;Sherwood et al, 2008aSherwood et al, , 2008bRoseman et al, 2010). The vertebrate cranium is comprised of three major developmental components: the splanchnocranium (comprising the jaws, hyoid, and middle ear bones) the chondrocranium (supporting the brain and sensory organs) and the dermatocranium (comprising the roof and sides of the cranium) (Kardong, 1995;Hildebrand and Goslow, 2001;Webster and Webster, 2013).…”
Section: Craniofacial Integrationmentioning
confidence: 99%
“…Second, given their evolutionary proximity to us, OWMs are a relevant evolutionary (Jolly, 2001) and biomedical model for humans (VandeBerg et al, 2009). Consequently, we have an increasingly good understanding of the genetic underpinnings of OWM skeletal variation (Havill et al, 2005;Sherwood et al, 2008aSherwood et al, , 2008bKoh et al, 2010;Roseman et al, 2010;Joganic et al, 2012;Hlusko, 2016;Hlusko et al, 2016). Third, there is an abundant Plio-Pleistocene fossil record (Jablonski, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These were phenotyped in the same manner as the human cephalographs although a portion of the phenotypes do not translate onto the shape of the baboon skull; therefore, there are fewer traits measured in this sample. Recent work (Sherwood et al 2008c has shown that the craniofacial traits in the baboon, similar to those in the human study, are all significantly heritable.…”
Section: Current Work On the Quantitative Genetics Of The Human And Nmentioning
confidence: 66%
“…Ten significant QTLs were identified for human craniofacial traits (Sherwood et al 2004, and 14 QTLs were identified for baboon craniofacial traits (Sherwood et al 2008c). Many of the regions identified in both species contain genes known to influence craniofacial features (e.g., SIX3, OTCS, BMP6, or several members of the WNT family).…”
Section: Current Work On the Quantitative Genetics Of The Human And Nmentioning
confidence: 99%
“…For example, hybridization between yellow baboons and anubis baboons is known to influence morphological traits in the wild [94]. A QTL mapping study in captive baboons (a colony that also includes anubis-yellow hybrids) has identified candidate regions of the genome that influence morphological variation [95], providing insight into the possible basis for this effect. As the genetic basis for such traits becomes more clear, checking for consistency between multiple populations should therefore be of considerable interest.…”
Section: Additional Materialsmentioning
confidence: 99%